NOD2 regulates CXCR3-dependent CD8(+) T cell accumulation in intestinal tissues with acute injury - Wu, Xingxin (2014)
Polymorphisms in NOD2 confer risk for Crohn’s disease (CD), characterized by intestinal inflammation. How NOD2 regulates both inflammatory and regulatory intestinal T cells, which are critical to intestinal immune homeostasis, is not well-understood. Anti-CD3 monoclonal antibody (mAb) administration is used as therapy in human autoimmune diseases, as well as a model of transient intestinal injury. The stages of T cell activation, intestinal injury, and subsequent T tolerance are dependent on migration of T cells into the small intestinal (SI) lamina propria. Upon anti-CD3 mAb treatment of mice, we found that NOD2 was required for optimal small intestinal IL-10 production, in particular from CD8(+) T cells. This requirement was associated with a critical role for NOD2 in SI CD8(+) T cell accumulation and induction of the CXCR3 ligands CXCL9 and CXCL10, which regulate T cell migration. NOD2 was required in both the hematopoietic and non-hematopoietic compartments for optimal expression of CXCR3 ligands in intestinal tissues. NOD2 synergized with IFN-γ to induce CXCL9 and CXCL10 secretion in dendritic cells, macrophages and intestinal stromal cells in vitro. Consistent with the in vitro studies, during anti-CD3 mAb treatment in vivo, CXCR3 blockade, CD8(+) T cell depletion or IFN-γ neutralization each inhibited SI CD8(+) T cell recruitment, and reduced chemokine expression and IL-10 expression. Thus NOD2 synergizes with IFN-γ to promote CXCL9 and CXCL10 expression, thereby amplifying CXCR3-dependent SI CD8(+) T cell migration during T cell activation, which in turn contributes to induction of both inflammatory and regulatory T cell outcomes in the intestinal environment.